Penerapan Kompetensi Spencer Pada Aparatur Sipil Negara - Anak Agung Made Diah Wijayanthi (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTThe purpose of this study was to find out how the method of developing human resource competencies with the Spencer theory approach for employees and to find out how the application of Spencer's theory in evaluating the competencies of employees. This study uses a qualitative approach with descriptive analysis method. Data collection techniques used are observation, interviews with informants and documentation. The selection of informants is done by purposive sampling method. The results of the study show the model of human resource competency development with the Spencer theory approach for contract employees at the City Youth and Sports Education Office in Denpasar through training and training to contract employees in performing assigned tasks to improve their competency. The application of Spencer's theory in competency evaluation of contract employees at the Department of Youth and Sports Education in Denpasar City is good because contract employees can complete their responsibilities on time. Competency development Achievement orientation cannot be done maximally because there are complaints from contract employees regarding compensation in the form of wages. The wage already has standards regulated by the local government as well as laws that cannot be easily changed. Future research is expected to be able to use more competency indicators in terms of evaluating employee performance by adding other theories and adding other factors of competence that can be used in evaluating an employee's performance.